Effects of two-months balanced diet in metabolically healthy obesity: lipid correlations with gender and BMI-related differences - Rondanelli, Mariangela (Lipids Health Dis, 2015)
BACKGROUND: Nowadays no researches has been performed on fatty acid profile (FA) and desaturase activity in metabolically healthy obesity (MHO). The aim of this study was to assessed gender and BMI-related difference in FA, estimated desaturase activities and the efficacy on metabolic changes produced by 2-months well-balance diet in MHO subjects. METHODS: In 103 MHO subjects (30/73 M/F; age:42.2 ± 9.5) FA, estimated desaturase activity, body composition (by DXA), Body Mass Index (BMI), lipid profile, adipokines (leptin, adiponectin, grelin, glucagon-like peptide-1), insulin resistence (by Homestasis metabolic assessment), C-reactive proteine, Atherogenic index of plasma (AIP) and Body Shape Index (ABSI) have been assessed. Gender and BMI related difference have been evaluated and the efficacy produced by 2-months well-balance diet has been considered. RESULTS: At baseline, obese subjects, compared to overweight, show a significantly higher oleic (p <0.050), monounsaturated fatty acids (p <0.040), C18:0 delta-9 desaturase activity (D9D) (p <0.040) and lower linoleic acid (p <0.020), polyunsaturated fatty acids (p <0.020) and n-6 LCPUFA (p <0.010). Concerning gender-related difference, women show a significantly higher arachidonic acid (p <0.001), polyunsaturated fatty acids (p <0.001), n-6 LCPUFA (p <0.002), and lower monounsaturated fatty acids (p <0.001), D6D activity (p <0.030), C18:0 D9D (0.000) and C16:0 D9D (p <0.030). The 2-months diet was associated with a significantly increase in arachidonic acid (p = 0.007), eicosapentaenoic acid (p = 0.030), docosahexaenoic acid (p <0.001), long chain omega 3 polyunsaturated fatty acids (n-3 LCPUFA) (p <0.001), delta-5 desaturase activity (D5D) (p = 0.002), glucagon like peptide-1 (p <0.001) and a significant decrease in palmitoleic acid (p = <0.030), n-6/n-3 LCPUFA (p <0.001), insulin resistance (p = 0.006), leptin (p = 0.006), adiponectin (p <0.001), grelin (p = 0.030), CRP (p = 0.004), BMI (p <0.001) and android fat mass (p <0.001). CONCLUSIONS: The balanced diet intervention was effective in improving metabolic indices.